Functional Annotation of Selected Vibrio cholerae Hypothetical Proteins - Yunos, S.N.S.M.; Hamid,A.A.A.; Zin,N.H.M.; Bunnori, N.M.; Yusof,H.A.; Kamarudin, K.R.; Rehan, A.M. (Universiti Sains Islam Malaysia, 2024)
Vibrio cholerae (V. cholerae) secreted an enterotoxin that induces acute diarrhea called cholera. Cholera if left untreated, lead to renal failure, shock, hypokalemia and pulmonary edema, which can cause death within hours. This disease occurs due to the bacterial virulence factors machinery. Previous studies have shown that the essential genes of V. cholerae O1 biovar El Tor N16961 strain are highly important in the bacterial growth, survival and its virulent properties. However, 45 of the essential genes were categorized as hypothetical genes with no known function and structure. Thus, this in silico study aimed to functionally and structurally annotate these essential hypothetical genes. All of the 45 hypothetical genes primarily underwent screening process for its pathogenicity and template availability. After screening, 11 of them were selected for further physicochemical categorization, functional and structural characterization using bioinformatics tools. From the data collected, all of the 11 hypothetical proteins are either involve in translation, cell transportation, cell growth or cell defense mechanism. All of the 11 hypothetical proteins were annotated, with five of them being the most promising proteins for further analysis. The finding of this study could provide an insight on the V. cholerae O1 biovar El Tor N16961 mechanism of pathogenesis, which could be useful for target identification for vaccine or drug design in order to reduce the fatality of cholera disease.